Building from Scratch: An Auto-ethnographic Approach for the Development of a Social Reporting Model. (3rd May 2020) - Zicari, Adrian; Perera-Aldama, Luis
ABSTRACT: This paper presents an auto-ethnographic account of the development of a social reporting model in Latin America. This model, named 'Value Footprint' (VF), was created by Luis Perera Aldama while partner at the Chilean office of BigOne, a Big Four audit firm. The VF social reporting tool explains how companies create and distribute value, similarly to other Value Added Statements models. The VF has now been in use for over 15 years in more than 20 large companies in Colombia, Mexico, Chile, and Uruguay. Luis, one of the co-authors of this paper, narrates the inside story of how a social reporting model is actually created, by presenting a thick description that places this story in its cultural and historical context. This paper explores the use of Auto-ethnography, a relatively new research method in social sciences, which has rarely been used in Accounting. This unique approach helps the reader to reflect on the lessons gained from this experience and its implications for future developments in social accounting, particularly in emerging markets.